GANDRUNG ANYAR - Fajarwati, Ni Nyoman Manik; Yulinis, Yulinis; Budiarsa, I Wayan (Jurnal IGEL : Journal Of Dance, 2021)
The creative of this dance work m tradicomes frosional cultural events, namely Gandrung dance in Banjar Bangun Urip, Batukandik Village, Nusa Penida District, Klungklung Regency, Bali. Gandrung Anyar is a dance work new creations created from development of the Gandrung dance movement pattems in Nusa Penida with an emphasis on an atmosphere of joy. The creation of this dance work uses the theory of imagination which means power to from a picture (image) and aesthetic theory which means beauty. The process of embodying the creative dance approach uses the method creation in the book Mencipta Lewat Tari by Y. Sumandiyo Hadi, translation from the book Creating Through Dance by Alma M. Hawkins with three stage, namely exploration, improvisation and formation. Exploration is a stage of thinking, imagining, and responding by doing creativ resource research, determines arable ideas and themes, conceptual design of arable, selection of dancer, seklection composers and accompaniment players and selection training sites. Improvisation is the stage of pouring the concept of work to dance actors and the probation period, strarting with nuasen. The last stage is the formation the stage of unifying and arranging movement patterns, arable structures, music and formation as a whole.This dance work is packaged in the form of creative dance with tolerance themes. Performed by five female dancers accompanied by gamelan Semara Pegulingan and uses fan properties. The realization of this dance work is expected to make every human being aware of the importance of tolerance who live in doing an activity together in order to get good results and give happines to evyone. Keywords: Gandrung Anyar, kreasi.